2016
DOI: 10.1016/j.ajog.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of quantitative fibronectin testing in combination with cervical length measurement in symptomatic women

Abstract: In women with threatened preterm birth, quantitative fibronectin testing alone performs equal to the combination of cervical length and qualitative fibronectin. Possibly, the combination of quantitative fibronectin testing and cervical length increases this predictive capacity. Cost-effectiveness analysis and the availability of these tests in a local setting should determine the final choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…There are publications comparing the predictive strength of qualitative and quantitative fFN measurements (16,17). A recent study showed that quantitative fFN test alone is equal effective to the combination of cervical length and qualitative fFN test (18). Although there is no statistically significance, the shorter cervical length was correlated with the higher likelihood of vaginal birth according to our results.…”
Section: Discussionsupporting
confidence: 49%
“…There are publications comparing the predictive strength of qualitative and quantitative fFN measurements (16,17). A recent study showed that quantitative fFN test alone is equal effective to the combination of cervical length and qualitative fFN test (18). Although there is no statistically significance, the shorter cervical length was correlated with the higher likelihood of vaginal birth according to our results.…”
Section: Discussionsupporting
confidence: 49%
“…59 The combination of quantitative FFN testing and CL assessment may further increase predictive value, but data remains limited to preliminary observational studies. 62 The use of quantitative FFN remains investigational 63 and is not yet commercially available for use in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we found that increased serum relaxin (> 1010 pg/mL) had a sensitivity of 58% for predicting preterm birth in women with a CL > 15 mm. In this context, the function of relaxin seems to be similar to that of cervicovaginal fibronectin, which is also not correlated with CL, and may improve the prediction of preterm birth in symptomatic women with a CL > 15 mm.…”
Section: Discussionmentioning
confidence: 97%